The breadwinner - Ellis, Deborah, 1960- (Toronto : Douglas & McIntyre ; Berkeley, CA : Distributed in the USA by Publishers Group West, 2001)
Because the Taliban rulers of Kabul, Afghanistan, impose strict limitations on women's freedom and behavior, eleven-year-old Parvana must disguise herself as a boy so that her family can survive after her father's arrest.
Keywords: Women's rights -- Fiction; Disguise -- Fiction; Survival -- Fiction; Afghanistan -- Fiction